People and their material environment in first millennium BCE Babylonia - Cousin, Laura; Quillien, Louise; Ramez, Manon (Peeters, 2023)
"This volume is dedicated to the material culture of Babylonia and its neighbouring regions as documented in cuneiform texts. It presents the results of research conducted in the framework of the Franco-Austrian collaborative project ANR-FWF Material Culture of Babylonia during the 1st millennium BC (MCB). The case studies presented here cover different aspects of the material environments in palatial, temple, and private contexts and consider material culture in a broad sense, concentrating not only on the physical nature of manufactured objects but also on the status of their makers, on their working conditions and technologies, and the contexts of production and consumption. They thus propose an approach to socio-economic history which focuses on the concrete and visible aspects of ancient society."
Introduction: "The present volume unites papers read in Paris at the workshop "Artefacts, Artisans et Techniques. Nouvelles approches contextuelles sur la culture matérielle au Proche-Orient ancien" at the 65e Rencontre Assyriologique Internationale in July 2019 ... as well as at the first international meeting of the Material Culture of Babylonia during the 1st millenium B.C. (MCB) project ... in December 2019 ..."
Introduction: "... The present book is the first of a series dedicated to material culture in Babylonia and its neighbouring regions, as documented in cuneiform texts dating from the first millennium BC ..."
Keywords: Sachkultur; Funde; Babylonien; Mesopotamien; Konferenzschrift -- 2019 -- Paris; Aufsatzsammlung